Energia renovável : benefícios alcançados frente aos investimentos em energia solar fotovoltaica no Campus Bento Gonçalves do Instituto Federal do Rio Grande do Sul - Ribeiro, Juliano (My University, 2026)
Global energy consumption is still predominantly supplied by fossil fuels, which imposes environmental and financial challenges on public organizations. In this context, solar photovoltaic energy has been consolidated as a strategic alternative for rationalizing resources and strengthening institutional sustainability. The present study aimed to identify the perceived benefits of investments in solar photovoltaic energy at the Bento Gonçalves Campus of the Federal Institute of Rio Grande do Sul (IFRS). This is an exploratory and descriptive research, with a predominantly qualitative approach, complemented by descriptive analysis of consumption data and energy costs in the period from 2020 to 2025. The results show an average reduction of approximately 16.5% in annual electricity costs after the full operation of the photovoltaic plant, in addition to a decrease in consumption from the conventional grid, greater budgetary predictability and strengthening of institutional energy autonomy. It was also observed that the installed infrastructure was integrated into teaching and management activities, consolidating the investment as a sustainable public innovation practice. It is concluded that the analyzed experience generated measurable economic benefits and strengthened organizational sustainability, establishing itself as a replicable model in the Federal Network of Professional, Scientific and Technological Education. [resumo fornecido pelo autor]
O consumo global de energia ainda é predominantemente suprido por fontes fósseis, o que impõe desafios ambientais e financeiros às organizações públicas. Nesse contexto, a energia solar fotovoltaica tem se consolidado como alternativa estratégica para racionalização de recursos e fortalecimento da sustentabilidade institucional. O presente estudo teve como objetivo identificar os benefícios percebidos frente aos investimentos em energia solar fotovoltaica no Campus Bento Gonçalves do Instituto Federal do Rio Grande do Sul (IFRS). Trata-se de pesquisa exploratória e descritiva, com abordagem predominantemente qualitativa, complementada por análise descritiva de dados de consumo e custos energéticos no período de 2020 a 2025. Os resultados evidenciam redução média de aproximadamente 16,5% nos custos anuais de energia elétrica após a operação plena da usina fotovoltaica, além de diminuição do consumo da rede convencional, maior previsibilidade orçamentária e fortalecimento da autonomia energética institucional. Observou-se ainda integração da infraestrutura instalada às atividades de ensino e gestão, consolidando o investimento como prática de inovação pública sustentável. Conclui-se que a experiência analisada gerou benefícios econômicos mensuráveis e fortaleceu a sustentabilidade organizacional, configurando-se como modelo replicável na Rede Federal de Educação Profissional, Científica e Tecnológica. [resumo fornecido pelo autor]
Keywords: Energia solar; Energia - Consumo - Aspectos econômicos; Sustentabilidade; Administração pública; Inovação; Solar energy; Energy consumption - Economic aspects; Sustainability; Public administration; Inovation